2016
DOI: 10.1530/rep-16-0097
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific prenatal stress effects on the rat reproductive axis and adrenal gland structure

Abstract: Social stress during pregnancy has profound effects on offspring physiology. This study examined whether an ethologically relevant social stress during late pregnancy in rats alters the reproductive axis and adrenal gland structure in post-pubertal male and female offspring. Prenatally stressed (PNS) pregnant rats (n=9) were exposed to an unfamiliar lactating rat for 10 min/day from day 16 to 20 of pregnancy inclusive, whereas control pregnant rats (n=9) remained in their home cages. Gonads, adrenal glands and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
11
3
Order By: Relevance
“…In addition, this ratio has been found to be finely modulated by sex hormones as for example androgens may affect both leptin and adiponectin levels (Lubkowska et al, 2015 ) and testosterone in particular has been shown to decrease adiponectin levels in rats (Nishizawa et al, 2002 ). In this regard, it is worth noticing that PNS is able to affect many aspects of sexual differentiation, including the concentrations of reproductive hormones (Ashworth et al, 2016 ). Thus, although we did not assess directly these parameters, we cannot exclude that PNS might set the ground for vulnerability to metabolic dysfunction by modulating sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this ratio has been found to be finely modulated by sex hormones as for example androgens may affect both leptin and adiponectin levels (Lubkowska et al, 2015 ) and testosterone in particular has been shown to decrease adiponectin levels in rats (Nishizawa et al, 2002 ). In this regard, it is worth noticing that PNS is able to affect many aspects of sexual differentiation, including the concentrations of reproductive hormones (Ashworth et al, 2016 ). Thus, although we did not assess directly these parameters, we cannot exclude that PNS might set the ground for vulnerability to metabolic dysfunction by modulating sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of stress type, a previous study by Guan et al [36] showed that the gestation length of dam Sprague-Dawley rats was not affected by maternal water deprivation for three days at late gestation. Another study by Alwasel [10] also showed that the gestation length of dam Wistar rats was not impacted by maternal food restriction. The body weights of stressed pregnant dams were significantly affected by water restriction during the last stages of pregnancy compared to control pregnant dams.…”
Section: Discussionmentioning
confidence: 91%
“…Various experimental studies conducted on mice, rats, and pigs showed that many environmental and ethological prenatal stressors can have injurious effects on the pregnancy and early and long-term adverse effects on the offspring. Different prenatal treatments and stress types, such as medications [1], drinking water restriction and deprivation [2][3][4], feed restriction [5], immobilization [6,7], light intensity [8], stocking density [9], restraint or social stressors [10][11][12][13][14][15][16], heat or noise [17], to which a pregnant female is exposed, can affect pregnancy outcome and influence many aspects of physiological systems in the offspring including sexual behavior, puberty onset, gonad function, reproductive hormones, and development of the reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, gestational exposure of rats to cold stress was found to reduce primordial follicle formation in the offspring either through reduced germinal nest breakdown or increase in oocyte apoptosis indicative of reduced ovarian reserve as well as decrease in the number of growing follicles suggestive of defects in the follicular activation / recruitment process (Barra, et al 2014). Likewise prenatal social stress in pigs (Ashworth, et al 2011) and rats (Ashworth, et al 2016) resulted in fewer primordial and more primary follicles, respectively, stressing the impact of maternal stress in programming offspring ovarian reserve and follicular activation. To what extent the impact of other stressors such as heat and bright light involve ovarian developmental defects in delaying vaginal opening and increasing estrus cycle length in the offspring (Politch and Herrenkohl 1984) remains to be ascertained.…”
Section: Basis Of Ovarian Pathologiesmentioning
confidence: 99%